Monitoring disease in England and Wales: methods applicable to routine data-collecting systems. Issue 4 (December 1978) - Fraser, R; Beral, V; Chilvers, C
Abstract : This paper reviews routine data-collecting systems and methods for disease surveillance in England and Wales. It discusses population-based correlation studies, which seek to explain disease trends by relating routine health statistics to possible causative agents on a secular, geographical, or occupational basis. It describes recent developments in linking information collected by routine general purpose systems as a means of identifying and following individuals exposed to potential hazards.